Temporal and spatial variability of total ozone content in Moldova: satellite retrievals and ground observations - Aculinin, Alexandr (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2010)
The total ozone content (TOC) values retrieved from measurements of spectral backscat-